Budgeting and financial management for national defense - McCaffery, Jerry; Jones, L. R. (Research in public management (Unnumbered), 2004)
Budgeting for national defense is a complex endeavor, particularly for a nation like the U.S. that assumes global responsibility and strives to have the most advanced and lethal force on earth. It is necessary - and challenging - to balance the myriad requirements between current and future readiness, across warfare areas and military services, between having state of the art capability with sufficient capacity, and among people, hardware, and the activities people do with that hardware. As analytically difficult as that problem is, it is embedded in the political budgeting processes and national security must be balanced with every other function of government and there must also be cooperation across branches of government. This text explores that complex endeavor.